Association of Knowledge and Presence of Pelvic Floor Disorders and Participation in Pelvic Floor Exercises: A Cross-sectional Study. Issue 5 (May 2021) - Goodridge, Sophia Delpe; Chisholm, Leah P.; Heft, Jessica; Hartigan, Siobhan; Kaufman, Melissa; Dmochowski, Roger R.; Stewart, Thomas; Reynolds, William Stuart
Abstract : Introduction: Women's baseline knowledge of pelvic floor exercises (PFEs) and pelvic floor disorders (PFDs) is not well established, as is their knowledge regarding PFE and participation in such exercise. The aim of our study was to assess baseline PFD and PFE knowledge and to determine if knowledge in any way influenced participation in PFEs. Methods: This was an institutional review board–approved, cross-sectional survey administered to women 18 years or older. We included all women who completed the survey, of which 3733 met the criteria. A survey-based questionnaire was used to query lower urinary tract symptoms, PFD, knowledge, and frequency of participation in PFEs. Results: Of those who responded, the mean incontinence knowledge score was 9.2 ± 2.6, whereas the mean score for pelvic organ prolapse (POP) knowledge was 6.8 ± 3.6. Of the respondents, 92.5% reported being familiar with Kegel exercises. The majority of respondents reported that they did not participate in PFEs (57.4%). Those with POP were more likely to do daily PFEs than those without POP, 34.8% versus 16.4% ( P < 0.001). Stress urinary incontinence did not influence frequency of performing PFEs. Conclusions: Our study demonstrated that while baseline knowledge of POP and incontinence knowledge were high in this patient population, the majority of participants did not participate in PFE. Participants with POP were more likely to partake in daily PFE. A gap exists between knowledge and willingness to participate in PFE. Bridging this gap may be significantly impactful for women's health.